Prevention of repeated episodes of type 2 reaction of leprosy with the use of thalidomide 100 mg/day - Maria Stella de Mello Ayres Putinatti; Joel Carlos Lastória; Carlos Roberto Padovani (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: Leprosy can have its course interrupted by type 1 and 2 reactional episodes, the last named of erythema nodosum leprosum (ENL). Thalidomide has been the medication of choice for the control of ENL episodes since 1965. OBJECTIVES: These episodes can repeat and cause damages to the patient. In order to prevent these episodes, an extra dose of 100 mg/day thalidomide was used during six months, followed by a follow-up period of six more months after thalidomide discontinuation. METHODS: We included 42 patients with multibacillary (MB) leprosy who had episodes of ENL. They were male and female patients aged between 18 and 84 years. RESULTS: Of the 42 patients, 39 (92.85%) had the lepromatous form and three (7.15%) had the borderline form. We found that 100% of patients had no reactional episode during the use of the drug. During the follow-up period after thalidomide discontinuation, 33 (78.57%) patients had no reactional episode and nine (21.43%), all of them with the lepromatous form, had mild episodes, which were controlled using non-steroidal anti-inflammatory. There were no thalidomide-related side effects. CONCLUSION: A maintenance dose of 100 mg/day of thalidomide showed to be effective to prevent repeated type 2 reactional episodes of ENL.